BRCA1 and BRCA2 Mutations Diagnostic and Therapeutic Implications - Valarmathi, Mani T. (IntechOpen, 2023)
Mutations in the BRCA1/2 genes are the most common cause of hereditary breast and ovarian cancer (HBOC), and HBOC is an autosomal dominant cancer predisposition syndrome. Individuals with HBOC have a high risk for breast and ovarian cancers and a moderate risk for other cancers, such as prostate, pancreatic, melanoma, and fallopian tube cancers. The goal of screening individuals at high risk of familial cancer is either prevention (such as a change in lifestyle or diet) or early detection of cancer. The identification of BRCA mutation carriers is important, since increased surveillance, drug therapy, and prophylactic surgery can reduce cancer-related morbidity and mortality. In recent years, there has been substantial development in BRCA-associated hereditary breast and/or breast-ovarian cancer research and its clinical applications. In this context, this book consolidates the recent advances in BRCA-related cancer biology and therapeutics, covering a wide spectrum of interrelated topics. Chapters cover a wide range of topics, such as BRCA discovery, BRCA structure and function, BRCA-associated cancers, BRCA genetic testing and counselling, and more. This book is a valuable resource not only for medical and allied health students but also for researchers, clinical and nurse geneticists, genetic counselors, and physician assistants.